2005
DOI: 10.1007/s00360-005-0046-7
|View full text |Cite
|
Sign up to set email alerts
|

Conditional mutations in SERCA, the Sarco-endoplasmic reticulum Ca2+-ATPase, alter heart rate and rhythmicity in Drosophila

Abstract: To analyze the role of cytosolic calcium in regulating heart beat frequency and rhythm, we studied conditional mutations in Drosophila Sarco-endoplasmic reticulum Ca 2+ -ATPase, believed to be predominantly responsible for sequestering free cytosolic calcium. Abnormalities in the amount or structure of the SERCA protein have been linked to cardiac malfunction in mammals. Drosophila SERCA protein (dSERCA) is highly enriched in Drosophila larval heart with a distinct membrane distribution of SERCA at cardiac Z-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 59 publications
5
44
0
3
Order By: Relevance
“…1). This is in line with previous measurements that range between 2.4 Hz and 4.5 Hz (Alex et al, 2015;Gu and Singh, 1995;Sanyal et al, 2006;Sénatore et al, 2010;Sláma and Farkaš, 2005). Several parameters influence heartbeat rate, i.e.…”
Section: Intracardiac Valve Cells -Mode Of Operationsupporting
confidence: 93%
“…1). This is in line with previous measurements that range between 2.4 Hz and 4.5 Hz (Alex et al, 2015;Gu and Singh, 1995;Sanyal et al, 2006;Sénatore et al, 2010;Sláma and Farkaš, 2005). Several parameters influence heartbeat rate, i.e.…”
Section: Intracardiac Valve Cells -Mode Of Operationsupporting
confidence: 93%
“…Yet, a similar connection has been described for a conditionally mutant SERCA form in Drosophila (49). Sanyal et al (49) found HR strikingly reduced when SERCA activity was inactivated. In addition, Rubio et al (47) also demonstrated the involvement of augmented Ca 2ϩ cycling in arrhythmogenesis after overexpression of SERCA1 in a L-type voltage-dependent calcium channel-overexpressing transgenic mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the Drosophila model has also been adopted to investigate cardiac physiology, performance and aging Sanyal et al, 2006;Wolf et al, 2006;Ocorr et al, 2007;Mery et al, 2008) using assays to determine the contractility, rhythmicity and other performance parameters, for example, stress assay, in which the cardiac performance is tested by using external electrical pacing of the heart rate (Paternostro et al, 2001;, ultrasound-like image analysis of the heart in intact flies [using optical coherence tomography (OCT); Wolf et al, 2006], digital high-speed video imaging of semi-intact adult fly heart, which in addition allows characterizing the contractility and rhythmicity of the heart (Ocorr et al, 2007). Using these assays, it was found that the fly homologue of the KCNQ1 potassium channel gene, which is associated with human cardiac arrhythmias and long QT, causes heart rhythm abnormalities also when mutated in flies, and they become more severe with age (Ocorr et al, 2007).…”
Section: Discussionmentioning
confidence: 99%